The US involvement in the Korean War:Causes and effects - ARSLANE, Dhahbiya (My University, 2018)
ABSTRACT The Korean warwas a unique crisis in the cold war that paved the way for US involvement. The dissertation sheds light on facts related to the US involvement in the Korean War. It examines the USpractice of Containment policy in the Cold War era, during the US involvement in the Korean War between 1950 -1953. The research, hence, aims to analyze both causes and consequences of the US involvement in the war Focusing on this issue , the first chapter gives an overview about the location, people and history of Korean peninsula . The second chapter explores the civil war between South and North Korea. Also, it discusses the reasons that led to the outbreak of the said war. The third chapter examines the role played by the US during the Korean war. It shows the reasons behind the US involvement. Furthermore, it outlines the main ideologies and tools used by the US during the war. Finally, the fourth chapter cites the results of the US involvement in the Korean war on both the USand the participants. The study uses descriptive analytical method of the available data to meet the stipulated objectives. All in all, the study examines the US ideology used to fight the spread of communism in the region and its tools,further more , the most important events that led to the outbreak of the civil war between Northern and Southern Korea.
Keywords: Key words : Korean war – soviet union : containment policy: US involvement: communism